Review Artikel: Standar Pelayanan Kefarmasian di Puskesmas Indonesia - Berlianna Nur Afiddah; Larasati Fauziah Yakub; Lisda Rahmawati; Janwar Janwar; Yudi Alfian; Indah Sari Amatun Nisa; Nia Yuniarsih (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the efforts to improve health development in Indonesia is to improve health services at puskesmas, especially pharmaceutical services, because health services at puskesmas are inseparable from pharmaceutical services which include management of pharmaceutical preparations and consumable medical materials (BMHP), this aims to find out suitability of pharmaceutical services at puskesmas, especially in the management of drugs and clinical pharmacy services using the literature review method by tracing various sources through Google Scholar. Based on the results of tracing data from several journals at puskesmas in North Minahasa Regency, Tamohon City, Bolaang Regency, Klari Health Center, Karawang Regency, Cirebon City, Batu City, Magelang Regency and Tanjung Karang Health Center, it can be seen that these puskesmas have not yet destroyed pharmaceutical supplies and consumable medical materials. as well as counseling clinical pharmacy services, visits and monitoring of drug side effects. So it can be concluded that some of these puskesmas have not implemented pharmaceutical services in accordance with pharmaceutical service standards listed in Permenkes number 74 of 2016 concerning pharmaceutical service standards at puskesmas.